2022
DOI: 10.1177/03611981221095513
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Recent Pedestrian Safety Patterns at Intersections through Crash Data Analysis

Abstract: Pedestrians are the most vulnerable road users and are at risk of severe consequences when involved in traffic accidents. The purpose of this research is to determine the factors that have significant impacts on the increasing likelihood of pedestrians being seriously injured or killed when involved in a collision with a single vehicle at an intersection over a recent 6-year period. Both 2013–2015 General Estimates System (GES) and 2016–2018 Crash Report Sampling System (CRSS) crash data were used in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The pedestrian overpasses and underpasses permit an uninterrupted flow of pedestrian movement separate from vehicle traffic [1]. Sometimes it is essential to fully separate pedestrians from vehicular traffic to improve their safety, as pedestrians are one of the most vulnerable road users with a high involvement in road accidents [1][2][3]. Research has shown that observing vulnerable road users' behavior has been largely ignored in the literature compared to drivers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pedestrian overpasses and underpasses permit an uninterrupted flow of pedestrian movement separate from vehicle traffic [1]. Sometimes it is essential to fully separate pedestrians from vehicular traffic to improve their safety, as pedestrians are one of the most vulnerable road users with a high involvement in road accidents [1][2][3]. Research has shown that observing vulnerable road users' behavior has been largely ignored in the literature compared to drivers [4].…”
Section: Introductionmentioning
confidence: 99%